2020
DOI: 10.1021/acssuschemeng.0c03979
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation Processing of Waste Cigarette Butts for High-Titer Bioethanol Production toward a Clean Recycling Process

Abstract: Proper disposal of large-quantity waste cigarette butts (WCBs) is of great importance for alleviating marine and land pollution, but it has been challenged by their complex compositions and toxic compounds contents. This work showed a technically feasible way to valorize WCBs through bioethanol production with high titers. Three deacetylation solvent systems, i.e., aqueous alkali, emerging alkali ethanol organosolv, and alkali deep eutectic solvent, were assessed for their abilities to produce high-purity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
0
18
1
Order By: Relevance
“…17,20 Based on these advantages, significantly improved biomass saccharification could be anticipated after deacetylation−steam pretreatment and subsequent enzymatic hydrolysis for efficient bioethanol production from lignocellulosic biomass. 22 In addition to the above insights, the structure and nature of lignin also have a considerable influence on the effectiveness of enzymatic hydrolysis. 23,24 It is found that during steam pretreatment, acetyl groups are released to form acetic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20 Based on these advantages, significantly improved biomass saccharification could be anticipated after deacetylation−steam pretreatment and subsequent enzymatic hydrolysis for efficient bioethanol production from lignocellulosic biomass. 22 In addition to the above insights, the structure and nature of lignin also have a considerable influence on the effectiveness of enzymatic hydrolysis. 23,24 It is found that during steam pretreatment, acetyl groups are released to form acetic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The reasons for the improved biomass saccharification by deacetylation have been previously investigated. It is shown that: (1) deacetylation decreases the degradation of hemicellulose and the formation of inhibitors, thus imposing less inhibition on cellulose hydrolysis; (2) deacetylation enhances the susceptibility of xylan to enzymatic degradation, ,, which could reduce biomass recalcitrance; (3) the partial removal of lignin and ash in deacetylation plays a role in increasing the biomass-specific surface area or introducing the substantial nanoscale porosity to biomass, ,, thus promoting the cellulose accessibility; , (4) deacetylation decreases the formation of acetic acid in pretreatment, which reduces the generation of pseudolignin and lignin droplets on the fiber surface. , Based on these advantages, significantly improved biomass saccharification could be anticipated after deacetylation–steam pretreatment and subsequent enzymatic hydrolysis for efficient bioethanol production from lignocellulosic biomass …”
Section: Introductionmentioning
confidence: 99%
“…Among these latters, cigarette filters represent a neglected and no cost reservoir of cellulose acetate 18 , that is virtually boundless if considering that about 5.5 trillion cigarettes are produced each year 19 21 . Notably, used cigarette butts (CBs) are considered a dangerous waste, because of the content of organic and heavy metals contaminants, therefore their use as starting raw materials is rather complex and essentially limited to production of asphalts, mesoporous carbon, and cellulose pulp 16 – 22 . Recently, bioethanol has been produced by fermentation of cellulose obtained by deacetylation of CBs 22 , but no attempts have been reported until now on their use to produce LA or other fine chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioethanol has been produced by fermentation of cellulose obtained by deacetylation of CBs 19 , but no attempts have been reported until now on their use to produce LA or other ne chemicals.…”
Section: Introductionmentioning
confidence: 99%